Extended equivalent dipole model for radiated emissions - Obiekezie, Chijioke S. (2016)
This work is on the characterisation of radiated fields from electronic devices. An equivalent dipole approach is used. Previous work showed that this was an effective approach for single layer printed circuit boards where an infinite ground plane can be assumed. In this work, this approach is extended for the characterisation of more complex circuit boards or electronic systems. For complex electronic radiators with finite ground planes, the main challenge is characterising field diffracting around the edges and boundaries. It is shown that this can be satisfactorily characterised using passive dipoles located along the edge. It is also shown that the number of dipoles used to characterise a device can be further optimised by using a complex location for the dipoles. Novel optimisation approaches such as particle swarm optimisation were also investigated. It is concluded that characterisation of complex electronic devices can be achieved in 3D space using edge dipoles to represent diffraction effects and available optimisation strategies.